Antidiabetic Activity of Ethanolic Extract of Pandan Tikar (Pandanus tectorius) on Alloxan-Induced Diabetic White Male Rats: (Uji Aktivitas Antidiabetes Ekstrak Etanol Daun Pandan Tikar (Pandanus tectorius) pada Tikus Putih Jantan Galur Wistar yang Diinduksi Aloksan) - Tanggu Rame, Magi Melia; Mbulang, Yohana K. A. (Universitas Tadulako, 2022)
Background: Diabetes mellitus is a chronic disease caused by the body's incapacity to use insulin or the inability of the pancreas to produce insulin. Pandan tikar, belong to Pandanaceae plants, has been known for its benefits. Chemical compounds in pandan tikar leaves showed that it has a lot of medicinal activities, one of them is to lower glucose blood level in diabetes mellitus. Objectives: This study aimed to determine the activity of ethanolic extract of pandan tikar (Pandanus tectorius) leaves as antidiabetic agent in white male rats induced by alloxan. Material and Methods: This study used a pretest-posttest design, with 25 Wistar white male rats. The rats were divided into five groups, each consisting of 5 rats. Group I, a positive control, was given glibenclamide with a dosage of 0.45 mg/kg BW. For the negative control, Group II, Na-CMC 1% was used. The test groups were Group III, IV, and V, and each received an ethanolic extract of pandan tikar leaves with various dosages of 125, 250, and 375 mg/kg body weight (BW), respectively. The rats were conditioned in diabetic stage by using alloxan 150 mg/kg bw as an inducer, given intraperitoneally, then each rats treated accordingly to their own group for 14 days. The determination of blood glucose level was done enzymatically by using glucometer. Result: The result showed that ethanolic extract of pandan tikar leaves able to lower the glucose blood level and not significantly different from glibenclamide. The most optimal dose of pandan tikar leaves ethanolic extract was 375 mg/kg bw, with the decreasing percentage was 56.72%. Conclusions: The ethanolic extract of pandan tikar leaves has antihyperglicemic ability on alloxan-induced diabetic white male rats.